Morfología externa e interna de la larva de Chiasmocleis leucosticta (Boulenger, 1888) (Amphibia, Anura, Mycrohylidae). - Langone, José A. (2007)
This contribution reports a comprehensive study of the tadpole of Chiasmocleis leucosticta, including external morphology, and, for the first time in the genus, the analysis of the bucco-pharingeal cavity, chondrocranium, visceral skeleton and histology of a peculiar structure of the tail. After the comparisson with other species of the genus and diverse species of the family, some structures are remarcable: (a) The anterior portion of the head bears a symmetrical line, similar in structure to a lateral line and in position to an orbitonasal line or nasolacrimal groove; (b) chondrocranium and visceral skeleton show a mixture of character states reported as typical for Types II and IV larvae; (c) the base of the tail has, as happen in other microhylid tadpoles, a peculiar thickenning, result of a particular development of the caudal dermis; (d) in the buccal cavity, the prenarial papilla is absent, the arena of the buccal roof bears several paillae and the glottis is placed in such a way that the prelingual area is the best developed. As a result, the tadpoles of C. leucosticta resemble more to diverse Asian than to the Neotropical microhylid larvae.